Low cost and renewable sulfur-polymers by inverse vulcanisation, and their potential for mercury capture. Issue 23 (6th December 2016) - Parker, D. J.; Jones, H. A.; Petcher, S.; Cervini, L.; Griffin, J. M.; Akhtar, R.; Hasell, T.
Abstract : Stable polymers of up to 80 wt% elemental sulfur are formed from low cost industrial by-products, and renewable crosslinkers. Abstract : Sulfur is not only a highly abundant element, but also produced as a by-product of the petrochemicals industry. However, it has not been conventionally used to produce functional materials because polymeric sulfur is unstable, and decomposes back to its monomer. Recently, inverse vulcanisation has been used to produce stable polymeric materials with elemental sulfur as a major component. Here we report a series of alternative crosslinkers for inverse vulcanisation that are either low-cost industrial byproducts, or bio-derived renewables. These are shown to produce stable polymers with superior properties to previously reported materials. When made porous by the action of supercritical carbon dioxide or salt templating, these high sulfur polymers show excellent potential for mercury capture and filtration.